2014
DOI: 10.1186/2041-9139-5-25
|View full text |Cite
|
Sign up to set email alerts
|

From dinosaurs to birds: a tail of evolution

Abstract: A particularly critical event in avian evolution was the transition from long- to short-tailed birds. Primitive bird tails underwent significant alteration, most notably reduction of the number of caudal vertebrae and fusion of the distal caudal vertebrae into an ossified pygostyle. These changes, among others, occurred over a very short evolutionary interval, which brings into focus the underlying mechanisms behind those changes. Despite the wealth of studies delving into avian evolution, virtually nothing is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 146 publications
(147 reference statements)
1
46
0
Order By: Relevance
“…During proper development, somites form as discrete units. However, segregation anomalies, where somites fail to establish proper borders, can ultimately lead to fully or partially fused vertebrae 8,21,22 , and thus could affect the number of pygostyle specific elements. To test whether somite segregation failure occurs in the pygostyle region, we examined distal somite morphology in the chick embryo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During proper development, somites form as discrete units. However, segregation anomalies, where somites fail to establish proper borders, can ultimately lead to fully or partially fused vertebrae 8,21,22 , and thus could affect the number of pygostyle specific elements. To test whether somite segregation failure occurs in the pygostyle region, we examined distal somite morphology in the chick embryo.…”
Section: Resultsmentioning
confidence: 99%
“…Mutational analyses have demonstrated that proper development of certain structures is critical to formation of a full length and/or unfused tail 8 . These structures include (but are not limited to) somites, intervertebral discs, intersomitic blood vessels, notochord, neural tube, cartilage, and neural crest; their breadth underscores the wide variety of genetic modifications that can result in a truncated tail and/or fused caudal vertebrae.…”
mentioning
confidence: 99%
“…), and tails are shown in left lateral view with the distal end towards the top (modified from Rashid et al . ). The arrows indicate the appearance of the features along the phylogenetic lineage leading to birds.…”
Section: Discussionmentioning
confidence: 97%
“…It has been hypothesized that having polyurals (more than two ural elements) is more primitive compared to the diural condition (60); all individuals go through some fusion of the urals after they are formed as individual centra, and fish ural fusion progresses as a slow process (60,63). Avian tails have also undergone considerable changes, from the plesiomorphic long tails of nonavian dinosaurs to the short tails with a fused pygostyle of birds (the group Pygostylia; this includes modern birds) as an adaptation for flight (64)(65)(66). During the embryonic period, pygostyle vertebrae chondrify, mineralize, and then fuse once the bird hatches (66).…”
Section: Discussionmentioning
confidence: 99%